1995
DOI: 10.1042/cs0890601
|View full text |Cite
|
Sign up to set email alerts
|

Septic Patients in Multiple Organ Failure Can Oxidize Infused Glucose, but Non-Oxidative Disposal (Storage) is Impaired

Abstract: 1. Patients suffering trauma and sepsis are insulin resistant, but no studies have specifically been made of patients suffering multiple organ failure. 2. We have studied exogenous glucose utilization in multiple organ failure using a combination of the hyperglycaemic glucose clamp and indirect calorimetry to quantify glucose utilization in multiple organ failure, partitioning it into oxidative and nonoxidative disposal (storage). 3. Fourteen septic patients with multiple organ failure were studied. APACHE II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…69 Additionally, impaired non-oxidative glucose disposal probably results from reduced skeletal muscle glycogen synthesis. 70 Both excess cortisol 71 and epinephrine 72 reduce insulin-mediated glucose uptake. Cytokines such as TNFα, 73 and interleukin 1 74 inhibit postreceptor insulin signalling.…”
Section: Pathophysiologymentioning
confidence: 99%
“…69 Additionally, impaired non-oxidative glucose disposal probably results from reduced skeletal muscle glycogen synthesis. 70 Both excess cortisol 71 and epinephrine 72 reduce insulin-mediated glucose uptake. Cytokines such as TNFα, 73 and interleukin 1 74 inhibit postreceptor insulin signalling.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Other studies with subjects at rest, and under conditions of hyperglycemia or euglycemic-hyperinsulinemia, have confirmed increases in glucose oxidation, as well as nonoxidative glucose disposal. Peripheral tissues, probably muscle, are primarily responsible for the disposal of most of the infused glucose load (DeFronzo et al 1981;Ferrannini et al 1989;Green et al 1995;Shulman et al 1990). Studies using indirect calorimetry in combination with hepatic and femoral-vein cannulation, and the euglycemic insulin clamp, have shown that the major site of non-oxidative disposal of glucose given intravenously in normal subjects is muscle (DeFronzo et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin levels are usually within the normal or mildly elevated range, but are not sufficiently elevated to prevent hyperglycaemia. Hyperglycaemia may also be due to reduced nonoxidative glucose disposal that results from decreased muscle glycogen synthetase activity [2,3]. The hyperglycaemia is thought to ensure a ready supply of glucose to predominantly glucose-consuming cells, such as the wound, inflammatory cells and immune cells [4].…”
Section: The Metabolic Milieumentioning
confidence: 99%
“…Insulin resistance occurred after both elective open and laparoscopic cholecystectomy, and persisted for at least 5 days [6,7]. The overall amount of glucose oxidized may be decreased, despite a glucose oxidization pathway that is thought to be intact, because of the reduced rate of glucose uptake into the cell [3]. The incremental response to increases in insulin concentration is maintained [8], but the ability to reduce blood glucose concentrations per insulin concentration is markedly diminished [9].…”
Section: The Metabolic Milieumentioning
confidence: 99%